2014
DOI: 10.1186/s12967-014-0253-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of umbilical cord mesenchymal stem cell transplantation in treatment for sequelae of thoracolumbar spinal cord injury

Abstract: BackgroundUmbilical cord mesenchymal stem cells (UCMSCs) have a considerable advantage and potential in treating for central nervous system diseases and have become a novel alternative treatment for spinal cord injury. This study aims to compare the neurological function outcome of stem cell transplantation, rehabilitation therapy, and self-healing for sequelae of spinal cord injury.MethodsThirty-four cases of thoracolumbar spinal cord injury were randomly divided into three groups: the stem cell transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 23 publications
(19 reference statements)
1
73
1
1
Order By: Relevance
“…The hWJ-MSCs currently represent a promising cell type in regenerative medicine and are already being evaluated in various clinical trials, including SCI. 30 The in vitro 2D cell culture demonstrated that both types of ECM hydrogels promoted adhesion and proliferation of hWJ-MSCs.…”
Section: Discussionmentioning
confidence: 97%
“…The hWJ-MSCs currently represent a promising cell type in regenerative medicine and are already being evaluated in various clinical trials, including SCI. 30 The in vitro 2D cell culture demonstrated that both types of ECM hydrogels promoted adhesion and proliferation of hWJ-MSCs.…”
Section: Discussionmentioning
confidence: 97%
“…MSCs transplantations via different routes of administration have been widely studied in different species of SCI (spinal cord injury), and have been proven to produce beneficial effects following SCI (Table ). The systemic or intraspinal cord administration of MSCs significantly attenuates SCI in rodents (Chopp et al., ; Hu et al., ; Kao, Chen, Chio, & Lin, ; Lu, Jones, & Tuszynski, ; Okano et al., ; Satake, Lou, & Lenke, ), dogs (Penha et al., ), rabbits (Moon et al., ), monkeys (Deng et al., ), or patients (Arien‐Zakay et al., ; Cheng et al., ; Jiang et al., ; Mendonça et al., ). MSCs are beneficial in reversing the neurological motor deficits of SCI, even when infused 5 days after injury (Saporta et al., ).…”
Section: Therapy With Conditioned Medium From Cultured Mscs Improves mentioning
confidence: 99%
“…We used hWJ‐MSCs, as these cells represent an easily accessible source, with high potential for clinical applications. Moreover, a therapeutic benefit of hWJ‐MSCs in SCI alone as well as in combination with a biomaterial has been shown previously in several experimental and clinical studies …”
Section: Introductionmentioning
confidence: 52%
“…Moreover, a therapeutic benefit of hWJ-MSCs in SCI alone as well as in combination with a biomaterial has been shown previously in several experimental and clinical studies. [35][36][37]…”
Section: Introductionmentioning
confidence: 99%